Appendages in zoo-housed animals: application of thermal imaging to study the thermal state of wildlife under human care - Adriana Domínguez-Oliva; Patricia Mora-Medina; Adriana Olmos-Hernández; Ismael Hernández-Avalos; Julio Martínez-Burnes; Carlos Gómez-Medina; Alejandro Casas-Alvarado; Daniel Mota-Rojas (Journal of Thermal Biology, 2026)

Gum Arabic as a functional feed additive in poultry and rabbits: a comprehensive review of growth, physiology, and stress resilience - Ayman H. Abd El-Aziz; Ahmed M. Elbaz; Daniel Mota-Rojas; Monsuru Oladimeji Abioja (Tropical Animal Health and Production, 2026)

Development of ingestive and social behavior of buffalo calves in a cow-calf contact grazing system - Arthur Fernandes Bettencourt; Francisco Freire Duarte; Isabelle Damé Veber Angelo; Daniel Mota-Rojas; Adriana Domínguez-Oliva; Vivian Fischer (Applied Animal Behaviour Science, 2025)

Facial action units as biomarkers of postoperative pain in ovariohysterectomized bitches treated with cannabidiol and meloxicam - Alejandro Casas-Alvarado; Julio Martínez-Burnes; Patricia Mora-Medina; Ismael Hernández-Avalos; Agatha Miranda-Cortes; Adriana Domínguez-Oliva; Daniel Mota-Rojas (Research in Veterinary Science, 2025)

Ingestive behavior of dairy buffaloes in a cow-calf contact grazing system during the post-calving - Arthur Fernandes Bettencourt; Francisco Freire Duarte; Isabelle Damé Veber Angelo; Júlia Fernandes Aires; Bruna Martins de Menezes; Anderson Michel Soares Bolzan; Daniel Mota-Rojas; Vivian Fischer (Applied Animal Behaviour Science, 2025)

Potential benefits of Ginkgo biloba in poultry nutrition: an updated review - Ayman H. Abd El-Aziz; Daniel Mota-Rojas; Bukola Christiana Majekodunmi; Monsuru Oladimeji Abioja (Tropical Animal Health and Production, 2025)

Analyses of the variable selection using correlation methods: An approach to the importance of statistical inferences in the modelling process - Mauricio Díaz-Vallejo; Alexander Peña-Peniche; Claudio Mota-Vargas; Javier Piña-Torres; Daniel Valencia-Rodríguez; Coral E. Rangel-Rivera; Juliana Gaviria-Hernández; Octavio Rojas-Soto (Ecological Modelling, 2024)

Anatomical and functional basis of facial expressions and their relationship with emotions in horses - Barbara Zimmermann; Alejandra Nelly Cristina Castro; Pamela Anahí Lendez; Mariano Carrica Illia; María Paula Carrica Illia; Alfredo Raúl Teyseyre; Juan Manuel Toloza; Marcelo Daniel Ghezzi; Daniel Mota-Rojas (Research in Veterinary Science, 2024)

Effect of heat stress on TNF-α, TNFRI and TNFRII expression in BLV infected dairy cattle - Pamela Anahí Lendez; Lucía Martínez Cuesta; María Victoria Nieto Farías; Adrián Alejandro Vater; Marcelo Daniel Ghezzi; Daniel Mota-Rojas; Guillermina Laura Dolcini; María Carolina Ceriani (Journal of Thermal Biology, 2023)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.